An exploration of the potential utility of fetal cardiovascular MRI as an adjunct to fetal echocardiography. (31st August 2016) - Lloyd, David F. A.; van Amerom, Joshua F. P.; Pushparajah, Kuberan; Simpson, John M.; Zidere, Vita; Miller, Owen; Sharland, Gurleen; Allsop, Joanna; Fox, Matthew; Lohezic, Maelene; Murgasova, Maria; Malamateniou, Christina; et al.
Abstract: Objectives: Fetal cardiovascular magnetic resonance imaging (MRI) offers a potential alternative to echocardiography, although in practice, its use has been limited. We sought to explore the need for additional imaging in a tertiary fetal cardiology unit and the usefulness of standard MRI sequences. Methods: Cases where the diagnosis was not fully resolved using echocardiography were referred for MRI. Following a three‐plane localiser, fetal movement was assessed with a balanced steady‐state free precession (bSSFP) cine. Single‐shot fast spin echo and bSSFP sequences were used for diagnostic imaging. Results: Twenty‐two fetal cardiac MRIs were performed over 12 months, at mean gestation of 32 weeks (26–38 weeks). The majority of referrals were for suspected vascular abnormalities (17/22), particularly involving the aortic arch ( n  = 10) and pulmonary vessels ( n  = 4). Single‐shot fast spin echo sequences produced 'black‐blood' images, useful for examining the extracardiac vasculature in these cases. BSSFP sequences were more useful for intracardiac structures. Real‐time SSFP allowed for dynamic assessment of structures such as cardiac masses, with enhancement patterns also allowing for tissue characterisation in these cases. Conclusions: Fetal vascular abnormalities such as coarctation can be difficult to diagnose by using ultrasound. Fetal MRI may have an adjunctive role in the evaluation of the extracardiac vascular anatomy and tissue characterisation. © 2016 The Authors. Prenatal Diagnosis published by John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Fetal cardiac MRI offers the potential to be a safe adjunct to echocardiography; however, there is no consensus on routine fetal indications or technical protocols for cardiovascular MRI in clinical practice. Previous studies have focused mainly on its utility for intracardiac imaging. What Does This Study Add? Abnormalities involving the extracardiac vasculature were the most common group of referrals for additional imaging in clinical practice. Fast spin echo MRI sequences offer the potential for better visualisation of these structures than ultrasound alone. Additional MRI benefits such as tissue characterisation can add further value in selected cases.